Advertisement Remove all ads

In ΔABC, prove that : tan((a-b)/2)=(a-b)/(a+b) cotC/2 - Mathematics and Statistics

In ΔABC, prove that : `tan((a-b)/2)=(a-b)/(a+b)cotC/2`

 

 

Advertisement Remove all ads

Solution

In ΔABC by sine rule, we have

`a/sinA=b/sinB=c/sinC=k`

a=ksinA,b=ksinB and c=ksinC

Now, consider

`(a-b)/(a+b)=(ksinA-ksinB)/(ksinA+ksinB)`

`=(sinA-sinB)/(sinA+sinB)`

`=(2cos((A+B)/2).sin((A-B)/2))/(2sin((A+B)/2).cos((A-B)/2))`

`=cot((A+B)/2).tan((A-B)/2)`

`=cot(pi/2-C/2).tan((A-B)/2) .....[because A+B+C=pi]`

`=tan(C/2)tan((A-B)/2)`

`(a-b)/(a+b)=tan((A-B)/2)/cot(C/2)`

`tan((A-B)/2)=(a-b)/(a+b)cot(C/2)`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×